ПРАГМАТИЧНІ ТА ПРАКСЕОЛОГІЧНІ ОСНОВИ ДОСЛІДЖЕННЯ РОЗСЛІДУВАННЯ ВІЙСЬКОВИХ ЗЛОЧИНІВ - Бершов, Геннадій Євгенович (SUPREMANCE OF LAW, 2017)
The article emphasizes that proposals for optimizing the activities of subjects authorized to carry out pretrial investigation of war crimes, in general and/or during individual procedural, organizational and other actions in the course of such an investigation, are developed by forensic science. Emphasis is placed on the importance of scientific developments in the outlined field being commensurate with the needs of practice, available resources, and the latest achievements in the field of science and technology. It is substantiated that a comprehensive study of the theoretical (ideological) and practical components of the investigation of war crimes makes it possible not only to obtain thorough and meaningful conclusions, but also to adapt them to the practical needs of law enforcement agencies and everyday use during the investigation of isolated offenses.
Keywords: war crimes; pragmatism; praxeology; pre-trial investigation; criminal proceedings; forensic recommendations